A multilocus phylogenetic framework of the tribe Aeromachini (Lepidoptera: Hesperiidae: Hesperiinae), with implications for taxonomy and biogeography. (3rd January 2019) - Huang, Zhen‐Fu; Chiba, Hideyuki; Jin, Ju; Kizhakke, Athulya Girish; Wang, Min; Kunte, Krushnamegh; Fan, Xiao‐Ling
Abstract: The Oriental tribe Aeromachini (Lepidoptera: Hesperiidae: Hesperiinae) is diverse and widespread, but its monophyly and circumscription remain unresolved. In this study, we inferred phylogenetic relationships within the tribe using two mitochondrial ( 16S and COI‐COII ) and two nuclear genes ( EF‐1α and Wingless ) from 71 samples representing all of the known genera of Aeromachini (s.l.). Phylogenetic topologies obtained from two model‐based methods (maximum‐likelihood and Bayesian inference) were largely congruent, showing that Aeromachini was monophyletic. Many genera within Aeromachini were polyphyletic, especially Arnetta, Thoressa, Ampittia and Sovia . Based on these results, we propose a new classification consisting of 14 genera, of which two are newly described: Halpemorpha gen.n. and Praethoressa gen.n. Ampittia and Ochus are restructured, with: (i) Ampittia nana and Ampittia dalailama moved to Aeromachus, (ii) new combinations proposed for the remaining Ampittia species, and (iii) a new combination, Ampittia subvittatus comb.n., proposed. The Oriental members of the genus Arnetta belong to this tribe, but the African Arnetta hyposticta was found to be embedded into the outgroup and closely related to Isoteinon . We propose that hyposticta be reinstated in the genus Galerga Mabille, along with two other African species ( fito and ellipsis ). Thoressa is polyphyletic, with three distinct lineages. The type species Thoressa masoni forms a clade closely related to the sister genera Sebastonyma and Parasovia . We thus describe Praethoressa gen.n. to include the species varia (formerly of Thoressa ), and transfer the remaining Thoressa to Pedesta, which is confirmed as a valid genus. Although the relationships of some genera remained unsolved in our work, the present phylogenetic hypothesis will serve as a reference for further studies. A secondary calibration was used to estimate the divergence time, which indicated that the diversification of Aeromachini started in the late Eocene and early Oligocene ( c . 34.22 Ma). Further, ancestral range estimates indicated that the common ancestor of Aeromachini originated in Southeast Asia. Diversification in situ and range expansion to adjacent areas have played essential roles in the evolution of Aeromachini, but founder‐event speciation and vicariance also have likely been important factors in shaping the biogeographical history of this tribe. This published work has been registered on ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:AA11191A-A4E2-47C5-B47B-445E6A2A9E5D . Abstract : Reconstruct the phylogeny of the tribe Aeromachini with expanded taxon sampling. Propose two new genera: Halpemorpha gen.n., and Praethoressa gen.n. Clarify taxonomic status of Arnetta and reinstate the African genus Galerga Mabille, rest.stat.